Current trends and available evidence on low-level laser therapy for osteoradionecrosis: A scoping review - Larissa Di Carvalho Melo; Bruna Bastos Silveira; Mylene Martins Monteiro; Juliana Amorim dos Santos; Elaine Barros Ferreira; Paula Elaine Diniz Reis; Camila de Barros Gallo; Eliete Neves Silva Guerra (Photodiagnosis and Photodynamic Therapy)
Background: This scoping review explored current trends and available evidence in Low-Level Laser Therapy (LLLT) in the treatment and prevention of osteoradionecrosis. Methods: The search strategy was conducted in MEDLINE/PubMed, EMBASE, Web of Science, and grey literature on January 15, 2024, without language or time restrictions. Results: 19 studies were included. The application of LLLT protocols was 58 % for therapeutic use, 21 % for preventive use, and 21 % for a combination of both. Regarding the use of antimicrobial photodynamic therapy (aPDT), 41 % of the studies employed this technique, which utilized methylene blue as the photosensitizer. For treatments associated with photobiomodulation, 57 % reported pharmacological treatment, 29 % surgical treatment, 11 % prescribed chlorhexidine mouthwashes, and 4 % other therapies. In vivo studies used diode lasers emitting low incident power densities in the near-infrared wavelength (67 %) at 780 to 904 nm. In comparison, case reports also used diode lasers emitting low incident power densities in the red and near-infrared wavelength (64 %) at 660 to 904 nm. The continuous emission mode was utilized in 83 % of in vivo studies and 17 % of the case reports. None of the studies included in this review reported all laser parameters. Conclusions: In general, studies suggested that LLLT can be used for therapeutic and preventive applications in the management of osteoradionecrosis. However, clinical studies are case reports and the variability in laser parameters across the included studies poses challenges for establishing standardized treatment protocols. The lack of comprehensive data on laser parameters underscores the need for future research to focus on standardizing LLLT protocols and conducting well-designed, large-scale clinical trials. This approach will help to better evaluate the effectiveness of LLLT and potentially integrate it more reliably into clinical practice.